A Study on Electric Vehicle Heat Pump Systems in Cold Climates - Ziqi Zhang; Wanyong Li; Junye Shi; Jiangping Chen (Energies, 2016)
Electric vehicle heat pumps are drawing more and more attention due to their energy-saving and high efficiency designs. Some problems remain, however, in the usage of the heat pumps in electric vehicles, such as a drainage problem regarding the external heat exchangers while in heat pump mode, and the decrease in heating performance when operated in a cold climate. In this article, an R134a economized vapor injection (EVI) heat pump system was built and tested. The drainage problem common amongst external heat exchangers was solved by an optimized 5 mm diameter tube-and-fin heat exchanger, which can meet both the needs of a condenser and evaporator based on simulation and test results. The EVI system was also tested under several ambient temperatures. It was found that the EVI was a benefit to the system heating capacity. Under a −20 °C ambient temperature, an average improvement of 57.7% in heating capacity was achieved with EVI and the maximum capacity was 2097 W, with a coefficient of performance (COP) of 1.25. The influences of injection pressure and economizer capacity are also discussed in this article.